2017
DOI: 10.1158/1078-0432.ccr-17-0438
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Vaccination after Accelerated Hypofractionated Radiation and Surgery in a Mesothelioma Mouse Model

Abstract: How best to sequence and integrate immunotherapy into standard of care is currently unknown. Clinical protocols with accelerated nonablative hypofractionated radiation followed by surgery could provide an opportunity to implement immune checkpoint blockade. We therefore assessed the impact of nonablative hypofractionated radiation on the immune system in combination with surgery in a mouse mesothelioma model. Blunt surgery (R1 resection) was used to analyze the short-term effect, and radical surgery (R0 resect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 44 publications
3
44
0
Order By: Relevance
“…The outcomes after induction chemotherapy followed by EPP and adjuvant hemithoracic radiation have been disappointing, with median survivals ranging between 16 and 20 months in trials that included more than 40 patients . However, patients who completed adjuvant hemithoracic radiation had a median survival of 29 to 39 months and achieved excellent local control . These results and studies in animal models and in vitro experiments suggest that, in contrast to current belief, mesotheliomas are sensitive to radiation .…”
Section: Treatmentmentioning
confidence: 87%
See 3 more Smart Citations
“…The outcomes after induction chemotherapy followed by EPP and adjuvant hemithoracic radiation have been disappointing, with median survivals ranging between 16 and 20 months in trials that included more than 40 patients . However, patients who completed adjuvant hemithoracic radiation had a median survival of 29 to 39 months and achieved excellent local control . These results and studies in animal models and in vitro experiments suggest that, in contrast to current belief, mesotheliomas are sensitive to radiation .…”
Section: Treatmentmentioning
confidence: 87%
“…Research in mice demonstrated that nonablative, hypofractionated radiation induces a specific activation of the immune system against mesothelioma with the development of an in situ vaccination, which is maintained through memory T cells directed against the tumor . Evidence from these mouse experiments and from palliative radiation in patients with mesothelioma suggest that a dose of radiation lower than 25 Gy in 5 fractions to the whole hemithorax may still be effective and limit the risks of pneumonitis in the underlying lung .…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…We then assessed the impact of local radiation on the immune system in combination with radical surgery in our mouse mesothelioma model to reproduce the SMART protocol (28). Blunt surgery and radical surgery were performed to analyze the short and long term impact of radiation and surgery.…”
Section: Radiation and Immunotherapy In Mesotheliomamentioning
confidence: 99%